Centenarians With Age-Related Macular Degeneration. (September 2017) - Stem, Maxwell S.; Mammo, Danny A.; Yonekawa, Yoshihiro; Todorich, Bozho; Thomas, Benjamin J.; Williams, George A.
Purpose: To report the clinical findings in patients ≥100 years old who have age-related macular degeneration (AMD). Methods: We identified patients ≥100 years old who had non-neovascular AMD, neovascular AMD or both. Results: Sixty-two patients were included. The mean (SD) age was 102 (1.4) years (range, 100-106 years). Most patients were white (n = 51, 82%), women (n = 51, 82%), and had at least 1 eye affected by neovascular AMD (n = 55, 89%). The mean Snellen visual acuity (VA) among eyes with neovascular AMD was worse than that for eyes with non-neovascular AMD (20/600 [range, 20/40-hand motions] vs 20/250 [range, 20/20-hand motions], respectively, P = .03). Eyes with an intact subfoveal ellipsoid zone (EZ) had much better mean VA than eyes with an absent or disrupted EZ (20/50 vs 20/500, P = .002). Conclusion: Most centenarians with AMD in our cohort had the neovascular form, and these individuals tended to have poorer vision than those with non-neovascular AMD. The presence of an intact subfoveal EZ is associated with better VA in eyes with neovascular or non-neovascular AMD compared to eyes with an absent or disrupted EZ.